Evaluation of the Prebiotic Effect of Chitin Extracted from Shrimp Waste by Bioremediation Method in Commercial Broilers - Subbarayudu, M; Ravi, A; Shakila, S; Ramana, J V (Indian Journal of Animal Nutrition, 2020)
Shrimp waste was recycled as a source of chitin and the extracted chitin was evaluated for its potential as a prebiotic in broiler birds. Chitin was extracted by the bioremediation method using lactobacillus culture and the protein rich liquid remaining after chitin extraction was recycled to enrich deoiled rice bran (DORB) to increase its crude protein content. The treated DORB was tested as an alternative to fish meal. The extracted chitin was characterized by FTIR spectroscopy. Four hundred commercial day old broiler chicks were divided into five groups of four replicates each with 20 birds per replicate and allotted at random to five experimental diets (T1 to T5) formulated for pre-starter (0-14 days), starter (14-28 days) and finisher (28-42 days) phases. The extracted chitin was included at 1 (T2) and 2% (T3). The treated deoiled rice bran was included at 3 (T4) and 6% (T5) to replace 50 and 100% fish meal of control diet (T1). The effect of treatments on growth performance of birds, gut pathogen (E. coli and Salmonella) load, RBC, WBC, Lymphocyte counts, serum and breast muscle cholesterol and triglyceride content was studied. The shrimp waste contained 26.69 % dry matter (DM) and the chemical constituents (% DM) were 40.5 (CP), 0.85 (EE), 28.65 (CF), 26.39 (TA), 6.78 (Ca), 3.03 (P), 63.76 (NDF), 54.46 (ADF), 9.28 (cellulose), 1.81 (ADL), 7.50 (silica) and 1.09 (kcal/g, TME). The overall growth performance of the birds was in the order of T3>T2>T1>T4>T5. There was a significant reduction (P<0.01) in caecal E.coli and Salmonella count , increase (P<0.01) in RBC, WBC and lymphocyte count and decrease in serum cholesterol and muscle triglyceride content of birds fed chitin containing diets. In conclusion, chitin was effective as a prebiotic during the pre starter and starter phases, more so at 2% than at 1% and the treated DORB was beneficial during finisher phase than during pre-starter and starter phases to replace 50 % of fish meal.